A multiaxial stress-based critical distance methodology to estimate fretting fatigue life. (April 2017) - Araújo, J.A.; Susmel, L.; Pires, M.S.T.; Castro, F.C.
Abstract: This work presents a methodology for fretting fatigue life estimation based on the evaluation of a multiaxial fatigue parameter at a critical distance below the contact surface. The fatigue parameter is defined using the Modified Wöhler Curve Method together with a measure of shear stress amplitude based on the Maximum Rectangular Hull concept. To apply the approach in the medium-cycle fatigue regime, the critical distance is assumed to depend on the fatigue life. Available fretting fatigue experiments conducted on a cylinder-on-flat contact configuration made of Al–4%Cu alloy were used to evaluate the methodology. Most of the fatigue life estimates were within factor-of-two boundaries. Highlights: Prediction of fretting fatigue lives using the Theory of Critical Distances. Material constants can be determined from standard fatigue tests. The approach accounts for the non-proportionality of the stress history. The approach accounts for the stress gradient in the contact region. Fretting fatigue lives of Al–4%Cu alloy were satisfactorily correlated.